Ask the Experts: Management of HIV-associated cognitive impairment. (July 2013) - Winston, Alan; Rackstraw, Simon
Alan Winston is a consultant physician in HIV and genitourinary medicine at St Mary's Hospital (London, UK) and a clinical senior lecturer at Imperial College London (UK). Dr Winston's research includes work on understanding the pathogenesis and epidemiology of comorbidities in relation to chronic HIV-disease with a focus on CNS pathology. He sits both on the British HIV Association and European AIDS Clinical Society writing groups on the management of cognitive impairment in HIV-disease. Simon Rackstraw is a consultant physician in HIV and genitourinary medicine at the Royal London Hospital (UK) and medical director at Mildmay Mission Hospital UK (London, UK). Dr Rackstraw's research includes work on understanding the epidemiology of cognitive impairment in HIV-infected patients and strategies for rehabilitation in those with HIV-related cognitive disorders.